Description of eight new species of the traumatically inseminating plant bug genus Coridromius (Heteroptera: Miridae: Orthotylinae: Coridromini) - Tatarnic, Nikolai Juris; Cassis, Gerasimos (European Journal of Taxonomy, 2013)
Eight new species of the plant bug genus Coridromius are described: C. basilanus sp. nov. from the Philippines, C. eremnos sp. nov. from Sabah, Malaysia, C. fomangsu sp. nov. and C. tafo sp. nov. from Ghana, C. norfolkensis sp. nov. from Norfolk Island, Australia, C. mulu sp. nov. from Sarawak, Malaysia, C. macchabeeus sp. nov. from Mauritius, and C. taravao sp. nov. from Tahiti, French Polynesia.